Structure and magnetoresistance of freshly condensed three-layer NiFe/Cu(Ag)/NiFe films - Loboda, V.B.; Shkurdoda, Yu.A.; Kravchenko, V.A. (Functional Materials, 2007)
Phase composition and magnetoresistive effect (the longitudinal and transversal magnetoresistance (MC) have been studied in freshly condensed three-layer FeNi/Cu(Ag)/FeNi films having dFeNi of 10 to 50 nm, dcu.Ag of 1 to 15 nm within temperature range of 150 to 400 K. The giant magnetoresistance effect has been shown to be realized in the unannealed three-layer films with a 3 to 15 nm thick non-magnetic interlayer. The temperature dependences of the longitudinal and transversal MR have been studied. The dependence of the magnetoresistance characteristic (ΔR/R₀)max, on the Cu and Ag interlayer thickness for the FeNi/Cu(Ag)/FeNi films has been established to show two maxima.